2023
DOI: 10.3390/toxics11020149
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Optimal Regulation of Sudden Water Pollution

Abstract: For the needs of the whole region’s emergency regulation of the nullah sudden water pollution event, the emergency regulation strategy of the accident section and upstream and downstream of the sudden water pollution event is studied. For the accident section, the duration of the whole emergency event is calculated using the parameter quantification method; for the upstream of the accident section, the NSGA-II is used to adjust the gate opening to ensure the water level stability of the upstream pools; for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…All three studies demonstrated that appropriate reservoir operation techniques reduced water supply loss during an SWP event. Nevertheless, the latter (Ren et al, 2023) acknowledged the limitation of the method due to insufficient universality in its applicability. Likewise, Vanda et al (2021) proved that emergency reservoir operation was often associated with complications due to the complicated goals and priorities that affected the decision‐making process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All three studies demonstrated that appropriate reservoir operation techniques reduced water supply loss during an SWP event. Nevertheless, the latter (Ren et al, 2023) acknowledged the limitation of the method due to insufficient universality in its applicability. Likewise, Vanda et al (2021) proved that emergency reservoir operation was often associated with complications due to the complicated goals and priorities that affected the decision‐making process.…”
Section: Resultsmentioning
confidence: 99%
“…Several benefits were observed from using reservoir operation or dispatch include avoiding pollution spread (Chen et al, 2021) and delaying of pollutant arrival time (Yu et al, 2018). It also helps in the dilution of pollutant concentration (Bing et al, 2021; Fang et al, 2018; Zhai et al, 2020) and prolonging of drinking water safety (Ding et al, 2019; Xiao et al, 2018), and supply (Liu et al, 2018; Ren et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation